Налогообложение валютных операций в Украине как инструмент валютной политики - Барсегян, А.Г. (Культура народов Причерноморья, 2013)
В данной статье рассматривается целесообразность применения фискальных инструментов для регулирования валютного курса в Украине. Приводятся рекомендации по оптимизации валютно-курсовой политики в Украине. У даній статті розглядається доцільність застосування фіскальних інструментів для регулювання валютного курсу в Україні. Наводяться рекомендації щодо оптимізації валютно-курсової політики в Україні. This article examines the usefulness of fiscal instruments for regulating the exchange rate in Ukraine. The basic disbalances of currency market of Ukraine are studied for the ground of application of measures of the administrative adjusting of rate of exchange. Among the most important factors of destabilization of the currency market are allocated low level of international reserves of the NBU, the devaluation expectations, lack of confidence in the national currency, the dollarization of the economy. Ukraine has already introduced administrative restrictions such as mandatory sale of 50% of export earnings, foreign exchange position limits for commercial banks with a maturity of revenue from exports, the identification of persons in the exercise of cash foreign exchange transactions. The monetary authorities of Ukraine to combat the negative foreign exchange processes are planning the introduction of a currency transaction tax, an analogue of the Tobin tax. In the world there are many examples of the application of the Tobin tax, but its effectiveness is often questionable. In Ukraine, there was already a currency transactions tax experience, which did not show a positive impact. For alignment of the currency market and stabilization of an exchange rate it is necessary market methods to limit influence of destabilizing factors and to stimulate economic and investment growth.